The Effect of Health Behavior and Nutrition Care Process on Estimated Glomerular Filtration Rate (eGFR) in Older Person with Chronic Kidney Disease at Subdistrict Health Promoting Hospital Nong-keaw Sisaket Province - Sansamak, Rapeephan; Hemha, Premrudee; Sae-tia, Yupawadee (Journal of The Royal Thai Army Nurses, 2025)
This quasi-experimental study with a two-group pretest-posttest design aimed to study the effects of health behavior and nutrition care programs on estimated Glomerular Filtration Rate (eGFR) in older adults with chronic kidney disease at Subdistrict Health Promoting Hospital Nong-Keaw, Sisaket Province. The sample consisted of 30 older adults with chronic kidney disease stages 1 to 4. Participants were selected through purposive sampling and divided into two groups of 15 each: an experimental and control. The groups were matched based on gender, age, and education level. The experimental group received the health behavior and nutrition care program for six weeks. Research instruments included health behavior and nutrition care program, demographic questionnaire, Mini-Mental State Examination - Thai version 2002, Barthel’s Index of Activities of Daily Living, Questionnaire on Perception of Food Consumption Behavior with a reliability score of .94, and an assessment form for estimated glomerular filtration rate (eGFR). The data were analyzed using percentage, mean, standard deviation, and t-tests with a significance level at .05. The results showed that tolder adults with chronic kidney failure in the experimental group had significant increase in eGFR after the intervention. Moreover, the eGFR of experimental groups was significantly higher than that of the control group after the intervention.